Resilience for Livestock by Displaced Farm Women in Hill Districts of Assam - Johari, Monosri; Saharia, K. K.; Khuman, L. Sanathoi (Indian Journal of Hill Farming, 2018)
A study on resilience practiced in rearing livestock by the displaced tribal farm women in hill districts of Assam was carried out by selecting one hundred respondents each from two districts of Assam namely Dima Hasao and Karbi Anglong through stratified random sampling, making the total sample size of 200. A pre-tested, reliable and valid interview schedule encompassing a check list containing eighteen items was used for data collection. It was found that that the average resilience measures for livestock was 22.85 out of the total obtainable score of 54. As such, the resilience measures for livestock were more or less in the medium range. The mean differences test revealed no significant variations in measures of resilience for livestock between the two districts. Further majority of the respondents revealed that they â€œkept the animals together in safer place whenever requiredâ€, â€œmaintained regularity in free grazingâ€, â€œprovided supplementary feed when in scarcityâ€, â€œtook special care for pregnant animals in feeding and husbandry practicesâ€ and â€œlargely interested in cross breeding and rearing of improved livestockâ€.